Combined effect of subchondral drilling and hyaluronic acid with/without diacerein in full-thickness articular cartilage lesion in rabbits - Suwannaloet W. (2014)
The osteochondral healing potential of hyaluronic acid (HA) plus diacerein was evaluated in subchondral-drilling- (SCD-) induced fibrocartilage generation in rabbits. A full-thickness chondral defect was created along the patellar groove of both knees and then SCD was subsequently performed only in the left knee. A week later, the rabbits were allocated into 3 groups to receive weekly intra-articular (IA) injection for 5 weeks with normal saline solution (NSS) (group 1) or with HA (group 2 and group 3). Starting at the first IA injection, rabbits were also gavaged daily for 9 weeks with NSS (group 1 and group 2) or with diacerein (group 3). The animals were then sacrificed for evaluation. The newly formed tissue in SCD lesions showed significantly better histological grading scale and had higher content of type II collagen in HA-treated group compared to NSS control. In addition, adding oral diacerein to HA injection enhanced healing potential of HA. © 2012 Wanwisa Suwannaloet et al.